2018
DOI: 10.3389/fphar.2018.01363
|View full text |Cite
|
Sign up to set email alerts
|

Value of Contrast-Enhanced Ultrasound and Acoustic Radiation Force Impulse Imaging for the Differential Diagnosis of Benign and Malignant Thyroid Nodules

Abstract: Objectives: To assess the value of contrast-enhanced ultrasound (CEUS) and acoustic radiation force impulse (ARFI) imaging for the differential diagnosis of benign and malignant thyroid nodules.Methods: CEUS was performed in eighty-eight thyroid nodules. The patterns of CEUS were analyzed, and ARFI was then performed. The shear wave velocities (SWVs) of the nodules and the surrounding normal thyroid tissue were obtained. The areas under the curve (AUCs) and cut-off value were obtained by a receiver operating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Five indicators were analyzed: arrival time, mode of entrance, echo intensity, homogeneity, and washout time. Within the subgroup of <10 mm there was a statistically significant difference between benign and malignant thyroid nodules for arrival time, mode of entrance and washout time; however, all five [30] indicators showed a statistically significant difference within the subgroup of >10 mm and the total group. The specificity for previously mentioned indicators ranged from 90-96% and diagnostic accuracy between 75-82%.…”
Section: Qualitative Analysis Of Ceus Enhancement Patternsmentioning
confidence: 74%
See 2 more Smart Citations
“…Five indicators were analyzed: arrival time, mode of entrance, echo intensity, homogeneity, and washout time. Within the subgroup of <10 mm there was a statistically significant difference between benign and malignant thyroid nodules for arrival time, mode of entrance and washout time; however, all five [30] indicators showed a statistically significant difference within the subgroup of >10 mm and the total group. The specificity for previously mentioned indicators ranged from 90-96% and diagnostic accuracy between 75-82%.…”
Section: Qualitative Analysis Of Ceus Enhancement Patternsmentioning
confidence: 74%
“…The most prominent features of nodules pointing to malignancy on CEUS were low enhancement and rim-like enhancement [58]. In contrast, other authors reported rim-enhancement as a pattern for benign nodules [30].…”
Section: Qualitative Analysis Of Ceus Enhancement Patternsmentioning
confidence: 90%
See 1 more Smart Citation
“…For CEUS, according to previous articles 21,25 and our clinical experience, thyroid nodules were evaluated with the following characteristics: homogeneity of enhancement, classified as homogeneous or heterogeneous; enhanced intensity (with respect to the surrounding normal thyroid parenchyma) was classified as hyper-enhancement, iso-enhancement or hypo-enhancement; ring enhancement (hyperechoic rim in the periphery of a nodule at the peak intensity), was classified as present (regular and complete) or absent (no, irregular or incomplete); enhanced border (the boundary between the nodule and the surrounding parenchyma at the peak intensity), was classified as welldefined or ill-defined; extrathyroidal extension (the thyroid nodule's enhancement range contacted/discontinued the hyperechoic thyroid capsule or extended out of the thyroid capsule) 26 was classified as no or yes (Figures 1C and 2C); centripetal enhancement (the contrast agent enters the nodule from the periphery of the nodule to the center), was classified as yes or no; the relative time of wash-in (using the surrounding normal thyroid parenchyma as a reference), was classified as earlier, concurrent, or later; and the relative time of wash-out time (using the surrounding normal thyroid parenchyma as a reference), was classified as earlier, concurrent, or later.…”
Section: Contrast-enhanced Ultrasoundmentioning
confidence: 99%
“…For example, contrast-enhanced US (CEUS) employs a microbubble agent to enhance the backscatter signals of red blood cells and can be used to characterize local vascular perfusion. Several studies have explored the perfusion patterns of thyroid nodules using CEUS (12)(13)(14). Elastosonography (ES) can be used to estimate malignancy by assessing the hardness of tissues (15).…”
Section: Introductionmentioning
confidence: 99%